Acceptance of internet banking among FELDA settlers in Bukit Tangga - Mohamad Azlan, Mohamad Nasrun (2013)
Using an already developed model for measuring the quality of online services and its acceptance, the author of this thesis has developed and later on modified a theoretical model (instrument) for measuring the quality and acceptance by people of online banking services particularly in FELDA Bukit Tangga. Using quantitative research method including the design and distribution of a set of questionnaire, empirical data was collected on which statistical analysis has been performed. As a result of the conducted analysis, the initial theoretical model has been modified, so that the final version of the model (instrument) for measuring quality and acceptance of online banking services includes four quality dimensions (Service Performance, Website Characteristics, Communication and Efficiency) with total of 29 items (questions). Furthermore, based on the modified theoretical model, people's acceptance with different aspects of the online banking services has been evaluated. Based on the results of the Analysis of the Empirical data, managerial recommendations are given. Suggestions for further research on internet banking acceptance were also offered